2018
DOI: 10.1186/s12993-018-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of reserpine-induced depression and cognitive disorder in zebrafish by sertraline and Traditional Chinese Medicine (TCM)

Abstract: BackgroundWith increased social pressure, individuals face a high risk of depression. Subsequently, depression affects cognitive behaviour and negatively impacts daily life. Fortunately, the Traditional Chinese Medicine Jia Wei Xiao Yao (JWXY) capsule is effective in reducing depression and improving cognitive behaviour.MethodsThe constituents of JWXY capsule were identified by ultra-performance liquid chromatography and quadrupole time-of-flight mass spectrometry analyses. We analysed behaviours of depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 46 publications
6
25
0
2
Order By: Relevance
“…Similar to wild type fish, the lepa KO fish also avoided yellow color, suggesting that the lepa KO fish was still able to distinguish different colors. The color preference of depression induced zebrafish was similar to that of the lepa KO fish pattern found in the present study, with no preference among blue, red and green color [88]. It has been reported that humans with depression are likely to choose neutral colors such as grey and black compared with healthy humans who would choose blue and red color [89].…”
Section: Discussionsupporting
confidence: 82%
“…Similar to wild type fish, the lepa KO fish also avoided yellow color, suggesting that the lepa KO fish was still able to distinguish different colors. The color preference of depression induced zebrafish was similar to that of the lepa KO fish pattern found in the present study, with no preference among blue, red and green color [88]. It has been reported that humans with depression are likely to choose neutral colors such as grey and black compared with healthy humans who would choose blue and red color [89].…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that the color of feed may affect the behavior of zebrafish [12]. Avoidance of yellow discovered in the present study is in line with earlier studies showing that zebrafish tend to avoid yellow [1,7,14]. Yellow has a higher light intensity compared with the other colors, which may contribute to the avoidance behavior in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Depression and anxiety have been linked with color preference changes in humans, and these changes have already been used to determine mental state in physiological studies [66]. Ethanol-treated fish showed a reduction in the choice index in the blue-yellow combination, similar to zebrafish depression behavior reported previously [14]. We also found that ethanol-treated fish exhibited a reduction in the choice index in the green-yellow combination.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, in this study, a color preference test was done to investigate whether lpar3 gene deficiency would affect the color preference and perception of zebrafish. Unfortunately, there are still some differences regarding zebrafish color preference ranking based on several previous studies that may be caused by the differences in the color wavelength, light source position, and luminescence applied in the prior studies [44][45][46][47][48][49][50][51]. However, before conducting the experiment, considerable numbers of wild-type fish were tested to observe their color preferences ranking in our test with the current setting.…”
Section: Lpar3 Ko Zebrafish Displayed Reduction Of Color Preferencementioning
confidence: 99%